2022
DOI: 10.1021/acsomega.2c01270
|View full text |Cite
|
Sign up to set email alerts
|

Rational Fabrication of Folate-Conjugated Zein/Soy Lecithin/Carboxymethyl Chitosan Core–Shell Nanoparticles for Delivery of Docetaxel

Abstract: The objective of this work is to design and fabricate a natural zein-based nanocomposite with core–shell structure for the delivery of anticancer drugs. As for the design, folate-conjugated zein (Fa-zein) was synthesized as the inner hydrophobic core; soy lecithin (SL) and carboxymethyl chitosan (CMC) were selected as coating components to form an outer shell. As for fabrication, a novel and appropriate atomizing/antisolvent precipitation process was established. The results indicated that Fa-zein/SL/CMC core–… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 68 publications
(116 reference statements)
0
14
0
Order By: Relevance
“…Effect of CMC dosage. In our previous study, 39 it was found that the content of CMC was crucial to the dispersity and stability of the obtained particles. In the AAP process, the solution of the solute was atomized into the antisolvent phase, resulting in the supersaturation of the solute, which is compensated by nucleation and particle formation.…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…Effect of CMC dosage. In our previous study, 39 it was found that the content of CMC was crucial to the dispersity and stability of the obtained particles. In the AAP process, the solution of the solute was atomized into the antisolvent phase, resulting in the supersaturation of the solute, which is compensated by nucleation and particle formation.…”
Section: Resultsmentioning
confidence: 89%
“…of the samples was recorded at 600 nm as the turbidity value. 39,40 Freshly-made ZLC suspensions with different CMC dosages before freeze-drying were measured at 25 °C which was repeated three times. Also the turbidity of the water redispersion of the freeze-dried ZLC NPs was measured to evaluate their redispersibility and stability.…”
Section: Fabrication Of Res/zlc Npsmentioning
confidence: 99%
“…With advancements in technologies pertaining to pharmaceutical sciences, various technological strategies, such as permeation enhancers, pro-drugs, and nanocarriers, have been employed to enhance the bioavailability of anti-neoplastic drugs after oral administration [7]. However, among the aforementioned approaches, nanocarrier-based oral Pharmaceutics 2022, 14, 1361 2 of 14 targeting strategies, especially protein-based nanocarriers, have received tremendous attention, owing to their unique advantages, such as ease of biodegradability, extraordinary drug-binding capacity, and the presence of numerous functional groups available for chemical modifications [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Due to high levels of hydrophobic amino acids in the structure, zein is water-insoluble but soluble in more than 50% ethanol solutions. In recent years, zein nanoparticles encapsulating hydrophobic drugs have been demonstrated to increase the bioavailability and treatment effect of water-insoluble drugs, such as rapamycin [ 11 ], resveratrol [ 12 ], quercetin [ 13 ], and docetaxel [ 8 , 14 ]. Although zein NPs were applied to tumor-targeted drug delivery with a high drug-loading capacity [ 8 ] and controlled-release properties [ 14 ], satisfactory intestinal absorption and anti-tumor efficacy could not be attained as zein NPs displayed poor colloidal stability in biological fluids and limited selectivity to tumor cells [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation